THE RHEOLOGICAL ANALYSIS OF BUCKWHEAT DOUGH FOR 3D PRINTING - Sadykov, Temirlan; Ospanova, Farida; Yermagambet, Adib (Nazarbayev University School of Engineering and Digital Sciences, 2025)
This research examines buckwheat dough rheological properties aiming to enhance their printability for 3D food manufacturing due to expanding market interest in gluten-free and sustainable clean-label products. Rheological characterization using oscillatory and steady shear rheometry examined the viscoelastic properties as well as flow behavior of buckwheat doughs with different water content levels combined with hydrocolloids including guar and xanthan gums. The Herschel–Bulkley model fitted the formulated doughs before printer tests were conducted on the Foodini 3D device to evaluate printability. Doughs containing 1% weight mass of guar gum and xanthan gum exhibited ideal elastic moduli ranges from 3 to 4.5 x 10⁴ Pa and yield stresses of 2 kPa which resulted in optimal shape retention together with stability properties. However, increased water content along with xanthan gum dosage impaired the structural properties. The tested doughs maintained print heights above 96% which validated their printing capabilities. Research findings present usable criteria to make printable gluten-free doughs which will help expand the functionality of 3D printing in food creation.
Keywords: rheology; buckwheat; dough; 3d printing; type of access: open access